A Chiroptical Logic Circuit Based on Self‐Assembled Soft Materials Containing Amphiphilic Spiropyran. Issue 8 (16th December 2015) - Liu, Changxia; Yang, Dong; Jin, Qingxian; Zhang, Li; Liu, Minghua
Abstract : A chiral logic circuit is proposed based on the multiple chiroptical responsiveness of a supramolecular gel material. The gel is fabricated by mixing a chiral gelator and a spiropyran derivative. Chiral responsiveness including the chiral switch and the logic gate is realized through the combined chirality transfer, photochromism, and acidichromism of the system.